Pengaruh Pelatihan Dan Motivasi Kerja Terhadap Kinerja Karyawan Pt Bank Bjb Kantor Cabang Khusus Jakarta - Eddy Kusnadi; Mahmud Syarif; Yudha Febri Al Paksi; Rachmat Fadly - Universitas Bina Sarana Informatika (APMMI - Asosiasi Profesi Multimedia Indonesia, 2020)
Abstrak-Companies that are ready to compete must have effective management. In addition to training and motivation, to improve employee performance in effective management requires the support of capable and competent employees in their fields. On the other hand, the development of employees includes what should be prioritized as the company's main asset. The learning process must be a corporate culture so that the skills of employees can be maintained, even improved. Based on the description above, a research can be submitted with the title